Oral susceptibility of Aedes aegypti (Diptera: Culicidae) from Senegal for dengue serotypes 1 and 3 viruses. Issue 11 (19th August 2014) - Gaye, Alioune; Faye, Oumar; Diagne, Cheikh T.; Faye, Ousmane; Diallo, Diawo; Weaver, Scott C.; Sall, Amadou A.; Diallo, Mawlouth
Abstract Objective To investigate the potential for domestic and wild populations of Aedes aegypti from Dakar and Kedougou to develop a disseminated infection after exposure to DENV‐3 and DENV‐1. Methods We have exposed sylvatic and urban population of Ae. aegypti from Senegal to bloomeals containing dengue serotype 1 and 3. At different incubation period, individual mosquito legs/wings and bodies were tested for virus presence using real time RT–PCR to estimate the infection and dissemination rates. Results The data indicated low susceptibility to DENV‐3 (infection: 2.4–15.2%, and dissemination rates: 0–8.3%) and higher susceptibility to DENV‐1 (infection and dissemination rates up to 50%). Conclusion Aedes aegypti from Senegal seem able to develop a disseminated infection of DENV‐1 and DENV‐3. Further studies are needed to test their ability to transmit the two serotypes.